Traditional knowledge of medicinal macrofungi commonly used by riverine populations of the Taï, Comoé and Marahoué national parks (Côte d’Ivoire) - Soro, Bakary; Kone, N’Golo Abdoulaye; Djoue, Alix Amenan; Bakayoko, Adama (Ethnobotany Research and Applications, 2026)
Background: Medicinal mushrooms are generally listed without specific therapeutic indications. This study aimed to enhance knowledge and practices regarding the use of medicinal mushrooms in the treatment of various ailments. Methods: An ethnomedicinal survey was conducted using a questionnaire focusing on local names, parts used, preparation methods, and routes of administration of macrofungi. The knowledge gathered was assessed based on the frequency of recipe citations and the relative level of exploitation of ethnopharmacological species. Results: This study reveals that women are the main holders of ethnopharmacological knowledge. The work focused on twelve species grouped by the informants into seven ethno-species. Species belonging to the genera Auricularia and lycoperdon were each considered a single ethno-species. The naming of ethnospecies is based on the shape of the sporophore, the color and the sociolinguistic affiliation of the users. These ethno-species are used in the treatment or relief of 28 conditions for which the ethno-medicinal recipes have been inventoried. The majority of conditions listed are treated using whole sporophores. The treatment of twelve conditions involves the combination of various inputs. The most common preparation method involves grinding the sporophores into powder. The method of administration of the recipes depends on the location of the condition. The analysis shows variability in the use of preparations and unequal exploitation of ethnospecies. Conclusions: This study highlights the wealth of ethnopharmacological knowledge about macrofungi. However, the gradual erosion of this knowledge among young people underscores the need to document and promote it. Keywords: Traditional knowledge, Medicinal macrofungi, Local communities, National parks, Côte d’Ivoire.